The current state and development trends of frailty research in diabetic patients: a bibliometric analysis - Ziqi Xu; Ziqi Xu; Rui Zhou; Xinran Zhou; Zhengyan Zhang; Qiong Li; Guodong Wang (Frontiers in Medicine, 2025)
BackgroundDiabetes mellitus is a global public health issue, often leading to organ damage, complications, and disabilities. Frailty is an age-related syndrome characterized by reduced physiological reserve and increased vulnerability to stressors, significantly affecting the prognosis of older diabetic patients. The prevalence of frailty is notably higher in older adults with diabetes than in those without. Therefore, a bibliometric analysis of research on diabetes-related frailty can provide deeper insights into the current state of this field and inform future research directions.MethodsThis study retrieved English-language publications on diabetes-related frailty from the Web of Science Core Collection (WOS) database, covering the period from 2005 to 2023. A total of 403 articles were included in the analysis. Statistical analysis and data visualization were conducted using Microsoft Excel, R Studio, VOS viewer, and Cite Space 6.3.R1. The analysis emphasized journals, authors, keywords, country collaborations, institutional collaborations, and references to elucidate trends and knowledge structures within the field of diabetes-related frailty research.ResultsThe number of publications on diabetes-related frailty has been steadily increasing each year, with research predominantly focused in developed countries, particularly the United States and Europe. The University of London has emerged as the institution with the highest volume of publications, while Alan J. Sinclair has been recognized as a significant contributor to this field. Key research hotspots include the complications associated with diabetes-related frailty, epidemiology, and quality of life. Additionally, a timeline analysis of references suggests that diabetic nephropathy is currently at the forefront of research in this area.ConclusionThis comprehensive bibliometric analysis of diabetes-related frailty research underscores the necessity for improved international collaboration to further investigate the mechanisms underlying diabetes-related frailty and to devise more effective prevention and treatment strategies. Future research should emphasize the relationship between diabetic nephropathy and frailty, as well as the development of personalized intervention programs tailored for frail diabetic patients.